The wedding guest [videorecording (DVD)] - Patel, Dev, 1990-; Apte, Radhika; Sarbh, Jim (IFC Films, 2019)
Jay is a man with a secret who travels from Britain to Pakistan to attend a wedding, armed with duct tape, a shotgun, and a plan to kidnap the bride-to-be. Despite his cool efficiency, the plot quickly spirals out of control, sending Jay and his hostage on the run across the border and through the railway stations, back alleys, and black markets of New Delhi, as all the while attractions simmer, loyalties shift, and explosive secrets are revealed.